2014
DOI: 10.1111/bph.12362
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics, pharmacokinetics and pharmacodynamics: interaction with biological differences between men and women

Abstract: Pharmacological response depends on multiple factors and one of them is sex-gender. Data on the specific effects of sex-gender on pharmacokinetics, as well as the safety and efficacy of numerous medications, are beginning to emerge. Nevertheless, the recruitment of women for clinical research is inadequate, especially during the first phases. In general, pharmacokinetic differences between males and females are more numerous and consistent than disparities in pharmacodynamics. However, sex-gender pharmacodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(158 citation statements)
references
References 205 publications
(210 reference statements)
2
150
0
6
Order By: Relevance
“…Most of the oral formulations have a definite proportion of estrogen and synthetic progesterone [29]. However, the composition of the OCs can vary from country to country so as the response toward the drugs forms the basis of pharmacogenomics [30]. The reports on the genotoxic potential in women's using steroid hormones as an OCs or HRT are available [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the oral formulations have a definite proportion of estrogen and synthetic progesterone [29]. However, the composition of the OCs can vary from country to country so as the response toward the drugs forms the basis of pharmacogenomics [30]. The reports on the genotoxic potential in women's using steroid hormones as an OCs or HRT are available [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the efficacy of AD medications, there is growing interest in investigating possible factors that mediate the response to pharmacotherapy, such as different patient characteristics and genetic factors [19,20] . It is notable that women and men vary largely in terms of biological and psychosocial-cultural factors involved in the response to medical treatments, and sex differences in response to medications have been described for several treatment methods [21][22][23][24][25] . For instance, it has been observed that women eliminate the hypnotic medication zolpidem more slowly than men do, and lower doses of this medication have been recommended for women compared to men [26,27] .…”
Section: Introductionmentioning
confidence: 99%
“…Literature has shown that females are more prone to develop adverse effects than males 27 . There is 1.5 to 1.7 folds increased risk of developing adverse drug reactions in women than men 28 .…”
Section: Resultsmentioning
confidence: 99%